2011
DOI: 10.1038/gt.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine therapy of thyroid carcinoma following Pax-8 gene transfer

Abstract: The thyroid transcription factor Pax-8 could bind with the promoter/enhancer of thyroid-specific genes such as thyroglobulin (Tg), thyroperoxidase (TPO) and sodium iodide symporter (NIS), and regulate the expression of these proteins in thyrocyte. Promoting iodide accumulation in tumor cells by re-expression of Pax-8 provides a possible strategy for radioiodine therapy of tumor. Therefore, we investigated the effect of Pax-8 gene transfer on radioiodine therapy of thyroid carcinoma. The human Pax-8 gene was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…These phenomena have also been found in the study by Xing et al, indicating that other factors may be involved in the regulation of the expression of Tg and Tpo . Moreover, TPO was not obviously elevated in our study, which may compromise the final lethal effect of radioiodine on tumour cells, due to that iodide anion not organized by TPO undergoes rapidly efflux from cells, and a balance between NIS‐mediated iodide uptake and TPO‐mediated efflux determines the intracellular concentration and radiation dose of radioiodine …”
Section: Discussionsupporting
confidence: 82%
“…These phenomena have also been found in the study by Xing et al, indicating that other factors may be involved in the regulation of the expression of Tg and Tpo . Moreover, TPO was not obviously elevated in our study, which may compromise the final lethal effect of radioiodine on tumour cells, due to that iodide anion not organized by TPO undergoes rapidly efflux from cells, and a balance between NIS‐mediated iodide uptake and TPO‐mediated efflux determines the intracellular concentration and radiation dose of radioiodine …”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that re-expression of PAX8 was associated with the recovery of the NIS mRNA expression in a rat thyroid cell line [42]. Furthermore, re-expression of PAX8 could promote iodine accumulation in human tumor cells [35,43]. The PAX8 and TTF1 are necessary to elevate levels of TSH [36].…”
Section: Discussionmentioning
confidence: 99%
“…For monolayer-cultured thyroid cells, and likely most thyroid cancer cells in patients, iodide organification may occur randomly at intracellular locations as the polarity of iodide influx and iodide efflux/organification may no longer exist. Pax-8 is the main transcription factor for Tg and TPO genes, and forced expression of Pax-8 by adenoviral vector in human anaplastic thyroid cancer cell lines, K-1 and F133, resulted in an increase in mRNA and protein levels of Tg and TPO, thereby resulting in an increase in iodide organification and retention [58]. Forced expression of both TTF-1 and Pax-8 further increased RAI uptake in K-1 and F133 cells by increasing NIS, Tg, and TPO expression levels [23].…”
Section: Modulation Of Nis-mediated Iodide Influx Iodide Efflux Andmentioning
confidence: 99%